Does a Session of Endurance Training with Three Different Intensities Affect the Cerebral Dopamine Neurotrophic Factor, superoxide dismutase, and malondialdehyde Levels of Cerebral Cortex in Male Rats? - Aslani, Ms. Jalil (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objectives: Parkinson’s disease through abnormalities in the body’s control centers causes symptoms such as tremor at rest, bradykinesia, muscular rigidity, and postural instability. The disease occurs due to the degeneration of cells secreting a substance called dopamine (catecholamine neurotransmitter). The purpose of this study was to investigate the effect of a session of endurance training with three different intensities on cerebral dopamine neurotrophic factor (CDNF), superoxide dismutase (SOD), and malondialdehyde (MDA) levels of cerebral cortex in male rats. Materials and Methods: The rats were divided into two main control and training groups. The training group consisted of low-, moderate-, and high-intensity trainings. The training groups (three groups with 24 rats in total), after getting acquainted with the rodent treadmill, were dealt with an acute training session with three different intensities. The CDNF level of the cerebral cortex was measured by ELISA assay, and the SOD and MDA levels of cerebral cortex by spectrophotometry. Data were analyzed using one-way analysis of variance and least significant difference post hoc test. Results: The acute training with different intensities significantly increases the CDNF and SOD levels of cerebral cortex and prevents the increase in MDA level of cerebral cortex.